CCN1 Regulates Chondrocyte Maturation and Cartilage Development. (March 2016) - Zhang, Yongchun; Sheu, Tzong‐jen; Hoak, Donna; Shen, Jie; Hilton, Matthew J; Zuscik, Michael J; Jonason, Jennifer H; O'Keefe, Regis J
ABSTRACT: WNT/β‐CATENIN signaling is involved in multiple aspects of skeletal development, including chondrocyte differentiation and maturation. Although the functions of β‐CATENIN in chondrocytes have been extensively investigated through gain‐of‐function and loss‐of‐function mouse models, the precise downstream effectors through which β‐CATENIN regulates these processes are not well defined. Here, we report that the matricellular protein, CCN1, is induced by WNT/β‐CATENIN signaling in chondrocytes. Specifically, we found that β‐CATENIN signaling promotes CCN1 expression in isolated primary sternal chondrocytes and both embryonic and postnatal cartilage. Additionally, we show that, in vitro, CCN1 overexpression promotes chondrocyte maturation, whereas inhibition of endogenous CCN1 function inhibits maturation. To explore the role of CCN1 on cartilage development and homeostasis in vivo, we generated a novel transgenic mouse model for conditional Ccn1 overexpression and show that cartilage‐specific CCN1 overexpression leads to chondrodysplasia during development and cartilage degeneration in adult mice. Finally, we demonstrate that CCN1 expression increases in mouse knee joint tissues after meniscal/ligamentous injury (MLI) and in human cartilage after meniscal tear. Collectively, our data suggest that CCN1 is an important regulator of chondrocyte maturation during cartilage development and homeostasis. © 2015 American Society for Bone and Mineral Research.